Character and costume in cinema: The Hollywood Costume exhibition. Issue 1 (1st June 2018) - Nadoolman Landis, Deborah
During a masterclass held in 2012, and in reference to her extensive publishing on film costume design, Deborah Nadoolman Landis invited the audience to also write on the subject, noting 'I ask my colleagues if I am to be the only one to fill the shelf with books on costume design and film'. Landis was the curator of the V&A exhibition, Hollywood Costume, the most comprehensive exhibition of its kind in decades. The exhibition analysed the extensive and detailed process employed to create a character through costume. Landis' paper, on 22 April 2012, launched a series of talks titled Marking the Paradigm Shift in Design for Performance Through Costume organized by Donatella Barbieri for the Research Hub in Design for Performance at London College of Fashion, University of the Arts London. The above quote and those that follow are edited with Landis from a transcript of the event.